Advanced competence in intensive care unit: expectations, role ambiguity between physicians and nurses in intensive care units. Multi - method survey. - Carbone, Roberta; Ferrari, Silvia; Belperio, Sara; Bravi, Sofia; Mancinelli, Camilla; Soave, Eleonora; Di Bartolomeo, Margaux; Andreassi, Laura; Perondi, Lorenzo; Tamba, Martina; Astolfi, Martina; Ossola, Cinzia; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The roles of physicians and nurses have undergone profound changes in recent years, becoming more complex and creating, at times, overlapping competencies with consequent negative repercussions in terms of problems related to autonomy and inter-professional collaboration. The study aims to detect the opinions of intensive care physicians and nurses with respect to their skills and role expectations. Method: The study was conducted in two phases. In the first phase, with a qualitative design, data were collected through the focus group. In the second phase, with quantitative design, an ad hoc questionnaire was constructed from the results of the previous phase. Results: 3 main themes emerged from the focus groups: the need to increase the system of inter-professional collaboration; autonomy and professional role; and the need for a shared advanced training system for physicians and nurses. The results of the questionnaire show that both professionals believe that the development of advanced skills does not lead to conflicting situations and role ambiguity unless the skills are recognized and respected. Both professionals agree that it is useful and necessary to implement a shared educational pathway. Conclusion: Inter-professional collaboration, specialist skills and specific training are a key element of the ICU teamwork.